Problems associated with the use of the Global Positioning System (GPS) by young fishermen in Malaysia - Omar, Siti Zobidah; Osman, Mohd Nizam; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
The main attempt of this study is to investigate the problems associated with the use by young fishermen in Malaysia of the Global Positioning System (GPS). This study is quantitative in nature and involved a total of 240 respondents who were young fishermen aged between 15 and 40 years. Individuals financial capacity to buy GPS was the main problem detected while the respondents also raised their concerns about a lack of GPS training programs, courses, seminars and promotional initiatives to further encourage the use of GPS within their fishing operations. The main recommendation made was to provide a technology subsidy to those who show an interest in buying GPS while additional funding should be allocated by the relevant parties to hold any programs, seminars, courses or promotional initiatives that can further encourage young fishermen in Malaysia to use advanced technology in their fishing operations.